2013
DOI: 10.1038/ng.2673
|View full text |Cite
|
Sign up to set email alerts
|

A haplotype map of genomic variations and genome-wide association studies of agronomic traits in foxtail millet (Setaria italica)

Abstract: Foxtail millet (Setaria italica) is an important grain crop that is grown in arid regions. Here we sequenced 916 diverse foxtail millet varieties, identified 2.58 million SNPs and used 0.8 million common SNPs to construct a haplotype map of the foxtail millet genome. We classified the foxtail millet varieties into two divergent groups that are strongly correlated with early and late flowering times. We phenotyped the 916 varieties under five different environments and identified 512 loci associated with 47 agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
351
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(379 citation statements)
references
References 38 publications
21
351
5
2
Order By: Relevance
“…Genome-wide association studies (GWAS), which seek to identify markers associated with a trait by large-scale genotyping of individuals differing for that trait, have recently been applied to cereal crop species with impressive results (Tian et al, 2011;Huang et al, 2012;Jia et al, 2013). GWAS may also be highly effective for the identification of brachypodium genes with roles in resistance to cereal disease.…”
Section: Future Prospects For Brachypodium As a Model For Cereal-pathmentioning
confidence: 99%
“…Genome-wide association studies (GWAS), which seek to identify markers associated with a trait by large-scale genotyping of individuals differing for that trait, have recently been applied to cereal crop species with impressive results (Tian et al, 2011;Huang et al, 2012;Jia et al, 2013). GWAS may also be highly effective for the identification of brachypodium genes with roles in resistance to cereal disease.…”
Section: Future Prospects For Brachypodium As a Model For Cereal-pathmentioning
confidence: 99%
“…Genetic diversity and population structure studies in Chinese green foxtail [24] and domesticated landraces [25] revealed high level of genetic diversity, an average allele number per locus of 33.5 and 20.9, respectively. A high density haplotype map of 85 million single nucleotide polymorphism (SNP) markers was also constructed, which revealed genomic variation among 916 foxtail millet accessions collected from around the world [5]. All these analyses provide the genomic data for the development of the Setaria model system.…”
Section: Promoting Setaria As a Modelmentioning
confidence: 99%
“…Given their hybrid fecundity, foxtail millet and green foxtail could be viewed as a single species with two botanical names. With a high quality reference genome sequence [4] and a high-density haplotype map of genome variation [5] and other genomic data, the accumulated genomic information for foxtail millet and green foxtail has reached the level where this species pair can now truly be considered a novel model system. Several publications, foxtail millet: a sequencedriven grass model system by Doust et al [6], Setaria viridis: a model for C 4 photosynthesis by Brutnell et al [7], and two review papers of using foxtail millet and green foxtail as model [8,9] have helped foster enthusiasm and forward momentum that is leading to the development of Setaria as a model system.…”
Section: Initiation Of the Setaria Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, compared to the limited magnitude in gene expression change that can be detected by microarray, the dynamic range of gene expression can be analyzed by RNA-seq is unprecedented [51]. Moreover, RNA-seq are used to characterize the single nucleotide variation (SNV) [52,53] and RNAediting activity in gene transcripts [54,55]. Notably, in regard to the non-model organisms that lack genome sequences, the RNA-seq technology is an extremely valuable tool.…”
Section: Second Generation Sequencing Versus Other Technologies In Trmentioning
confidence: 99%